A history of the study of grammar among the Syrians an English translation of Historia artis grammaticae apud Syros - Merx, Adalbert 1838-1909 (Perspectives on Linguistics and Ancient Languages, 2023)
This book is a translation of a monograph about the Syriac grammatical tradition, the Historia artis grammaticae apud Syros, by the 19th-century German theologian and linguist, Adalbert Merx. The book traces the ways in which Syriac scholars in Late Antiquity learned to analyse their own language and to adapt the techniques of Greek grammar to their own Semitic language. Starting with early translations of Greek works, Merx traces the innovations introduced by Jacob of Edessa and the development of accentuation and pointing. He also covers the contributions of Eastern and Western Syriac scholars such as Ḥunayn ibn Ishaq, Joseph bar Malkon, and John bar Zuʿbi, taking the story up to the time of Barhebraeus. The relationships of Syriac with Greek, Hebrew, and Arabic traditions are all carefully considered. The current edition has been extensively annotated in order to bring the reader up-to-date with research carried out since Merx published his ground-breaking work. The texts that were included in the original have also been re-published afresh, including the fragments of Jacob of Edessa's famous Grammar